2016
DOI: 10.1093/infdis/jiw364
|View full text |Cite|
|
Sign up to set email alerts
|

Adaptation of Mycobacterium tuberculosis to Impaired Host Immunity in HIV-Infected Patients

Abstract: Background. It is unknown whether immunosuppression influences the physiologic state of Mycobacterium tuberculosis in vivo. We evaluated the impact of host immunity by comparing M. tuberculosis and human gene transcription in sputum between human immunodeficiency virus (HIV)-infected and uninfected patients with tuberculosis.Methods. We collected sputum specimens before treatment from Gambians and Ugandans with pulmonary tuberculosis, revealed by positive results of acid-fast bacillus smears. We quantified exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Because hypoxia was detected in all samples tested, our data strongly suggest that the induction of dormancy is critical in all granuloma stages, a result supported by observations that lesions of macaques with both ATB and LTBI contain hypoxia ( Figures 4B-4D) (16). Our results are also supported by the recent evidence of dosR expression in the lungs of humans with TB (43). Overall, the pathogen's response to hypoxia is a critical component of its intragranulomatous physiology.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Because hypoxia was detected in all samples tested, our data strongly suggest that the induction of dormancy is critical in all granuloma stages, a result supported by observations that lesions of macaques with both ATB and LTBI contain hypoxia ( Figures 4B-4D) (16). Our results are also supported by the recent evidence of dosR expression in the lungs of humans with TB (43). Overall, the pathogen's response to hypoxia is a critical component of its intragranulomatous physiology.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, an unbiased, system-wide proteomic approach found that, upon in vitro hypoxic stress, 20% of all Mtb protein mass is contributed by the fewer than 50 dosR-regulated genes (48). Moreover, the expression of this regulon was recently reported to be strongly induced in human TB and to significantly lower levels in patients with HIV (43). This suggests that the expression of DosR may promote more robust granulomas, a contention supported by data that expression of DosR by WhiB6 promotes granuloma stability in an environment of chronic oxidative/nitrosative stress (49).…”
Section: Discussionmentioning
confidence: 99%
“…Because the risk of developing TB is largely increased in HIV-infected individuals even before CD4 T cell counts decrease ( 16 ), other factors must also play a role. Indeed, a detrimental alternative activation of macrophages, accompanied by less nitric oxide (NO) synthase expression and poorly formed granulomas was described in HIV–TB, which in turn downregulated the Mycobacterium tuberculosis DosR regulon ( 17 ), a set of genes known to be induced during anaerobic dormancy ( 18 ). Therefore, changes in the host immunity resulting from HIV coinfection remodel the bacterial physiology, further rewiring the host tissue microenvironment.…”
Section: The Modulation Of the Immune Response By Extrinsic Factorsmentioning
confidence: 99%
“…The authors observed increased expression of genes within the dormancy regulon in the cells collected by bronchoalveolar lavage (BAL) from HIV uninfected patients (Walter et al. 2016 ). The authors propose two possible explanations for this observation.…”
Section: The Dos System and The Dormancy Regulonmentioning
confidence: 99%
“…Increased expression of the arginase gene and a decreased expression of the gene for inducible nitric oxide synthase in HIV infected patients suggest that macrophages in HIV infected patients were potentially less capable of producing NO, stressing Mtb , and inducing the dormancy regulon in Mtb (Walter et al. 2016 ). Regardless, this finding underscores the importance of the host response on cellular activity of Mtb in human TB.…”
Section: The Dos System and The Dormancy Regulonmentioning
confidence: 99%